Legal Protection of Children's Rights Post-Divorce: A Study of Single Mothers in Malang Regency - Fardindaputri, Fairuza ‘Alima; Hasanudin, Fuat (Universitas Islam Indonesia, 2025)
This study critically examines the capacity of single mothers to enforce child support obligations against former husbands following divorce proceedings in Malang Regency, Indonesia. The research adopts a qualitative fieldwork approach, employing purposive (non-probability) sampling to select participants. Data were collected through in-depth interviews with divorced women who have legal custody of their children, specifically those whose children were minors at the time the divorce decree was issued. According to Article 41 of Law No. 1 of 1974 on Marriage and Article 156 of the Compilation of Islamic Law, the financial responsibility for the maintenance and welfare of children rests with the father until the child reaches the age of 21, marries, or becomes economically independent. However, the reality encountered by many single mothers deviates sharply from this legal expectation. Many ex-husbands fail to comply with child support obligations, leaving mothers to bear the full financial and emotional burden of child-rearing. Interviews revealed several contributing factors to this negligence, including the ex-husband’s lack of personal responsibility, economic incapacity, unknown whereabouts, and interference from third parties such as new spouses or family members. Although Indonesian law provides mechanisms for legal enforcement of child support, the findings indicate that very few single mothers pursue formal legal action. This reluctance is attributed to strained interpersonal relationships, concerns over the child’s psychological well-being, the complexity and cost of legal procedures, and a general lack of faith in the efficacy of the legal system. The study concludes that existing legal frameworks are insufficient to guarantee effective enforcement of child support, as there is no specialized legal policy tailored to the unique vulnerabilities faced by single mothers. This regulatory gap underscores the urgent need for legal reform that prioritizes the welfare of children and ensures compliance with parental responsibilities post-divorce.